Application of Stable Isotopes and Tritium in Hydrology (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This Special Issue “Applications of Stable Isotopes and Tritium in Hydrology” addresses the current state-of-the-art applications of stable isotopes and tritium in studies of hydrological process and the whole water cycle. The six scientific papers belonging to this SI show a wide variety of isotope applications in various studies performed locally or regionally, but the conclusions obtained may be valid worldwide. Precipitation, groundwater, and surface waters belong to classical water bodies, while evapotranspiration, effects of farming, and drip water in karst caves seldom present applications of water isotopes.